2010
DOI: 10.1161/circresaha.109.205906
|View full text |Cite
|
Sign up to set email alerts
|

The Vulnerability of the Heart As a Pluricellular Paracrine Organ

Abstract: In this review, we address clinical aspects and mechanisms of ventricular dysfunction induced byanticancer drugs targeted to the ErbB2 receptor. ErbB2 antagonists prolong survival in cancer, but also interfere with homeostatic processes in the heart. ErbB2 is a coreceptor for ErbB4, which is activated by neuregulin-1. This epidermal growth factor-like growth factor is released from endothelial cells in the endocardium and in the myocardial microcirculation, hence contributing to intercellular crosstalk in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(105 citation statements)
references
References 86 publications
1
104
0
Order By: Relevance
“…It has been long known that ErbB2 is expressed in embryonic hearts and has a critical role in cardiac development61 with relatively low expression in adult cardiomyocytes. Subsequent to the clinical trials showing cardiotoxicity from trastuzumab use, emerging research found that HER2 receptors expressed in the membranes of adult cardiomyocytes have an important role in transmitting growth and survival signals 62. In response to the ligand, neuregulin‐1, ErbB2 forms heterodimers that activate cell hypertrophy and survival pathways through activation of the phosphoinositide 3‐kinase and protein kinase A pathways as well as the mitogen‐activated protein kinase cascade 60, 63.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It has been long known that ErbB2 is expressed in embryonic hearts and has a critical role in cardiac development61 with relatively low expression in adult cardiomyocytes. Subsequent to the clinical trials showing cardiotoxicity from trastuzumab use, emerging research found that HER2 receptors expressed in the membranes of adult cardiomyocytes have an important role in transmitting growth and survival signals 62. In response to the ligand, neuregulin‐1, ErbB2 forms heterodimers that activate cell hypertrophy and survival pathways through activation of the phosphoinositide 3‐kinase and protein kinase A pathways as well as the mitogen‐activated protein kinase cascade 60, 63.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In adult heart, the most abundant ErbB receptors are ErbB2 and ErbB4 (Zhao et al, 1998), with HB-EGF and NRG-1 being important endogenous ErbB ligands. The influence of ErbB receptors on myocardial physiology was poignantly revealed in the cardiomyopathy observed in breast cancer patients receiving antibody inhibitors of ErbB2 (Ewer et al, 1999;De Keulenaer et al, 2010). Cardiac toxicity was noted in ~5% of these patients, increasing to >25% when co-administered with anthracyclines (Ewer et al, 1999;McKeage and Perry, 2002).…”
Section: Myocardial and Coronary Control Via The Egfrmentioning
confidence: 99%
“…Furthermore, N-terminally truncated ErbB2 (aka p95HER2, DNErbB2) lacks the Herceptin-binding site, rendering DNErbB2-overexpressing cancers resistant to Herceptin treatment (2,3). Herceptin resistance is also widespread in patients expressing full-length ErbB2 (4) and anti-ErbB2-treatments exhibit a range of potential side effects, including cardiotoxicity (5). Thus, despite the overall success of Herceptin, novel treatment regimens and combination therapies are needed.…”
Section: Introductionmentioning
confidence: 99%